ANALYSIS OF HEAT RELEASE RATE IN ENGINE ROOM FIRES OF 300 GT FERRY RO-RO PASSENGER BY USING WATER MIST SYSTEM AND CO2 SYSTEM - Setiawan, Wira; Distyan Kotanjungan (Deputi TIRBR-BPPT, 2021)
Based on statistical data in recent years, there are still quite a number of ship accidents due to fires, including on passenger ships. The water mist system is a fire suppression system that allows it to be used in the engine room with the advantage that it can keep the heat production rate low during the extinguishing process and can be operated earlier than the CO2 system. The research is conducted by using fire dynamic simulator in the engine room of a 300 GT ferry ro-ro passenger to compare the heat release rate of fire without an extinguishing system, an existing CO2 system, and a water mist system. The result shows that the CO2 fire suppression system reduces the heat release rate more rapidly to the decay phase at 375 seconds while the water mist takes more than 900 seconds. However, the fully developed phase of the water mist suppression system occurs more quickly than CO2 because the sprinklers are activated shortly after a fire occurs. Unlike water mist, the CO2 system is activated at 60 seconds so that the pre-combustion, growth, flashover, and fully developed phases are at the same HRR and time as the natural one.